Analisis Hasil Belajar Matematika Siswa di SMK Negeri 1 Umbunasi - Novetrianus Tafonao; Yulisman Zega (LP. Ma'arif Janggan Magetan, 2023)
The problem in learning mathematics is the assumption that most students perceive mathematics as a boring subject, so that many students do not like mathematics. The method used in this research was descriptive qualitative which was carried out at SMK Negeri 1 Umbunasi class X, Department of Office Management Automation, with a total of 31 students as subjects. The instruments used were 5 test questions and unstructured interview questions. Based on the results obtained, the percentage of students with very high scores was 3.22%, the percentage of students in the high category was 25.81%, the percentage of students in the medium category was 54.84% and the percentage of students in the low category was 16.13%.